Conjunctival rotational flap versus autograf t techniques in pterygium surgery at AL-Hussain teaching hospital from 2009-2015 - mehdy, Dr.Imad salih (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
purpose :the aim is to compare the results of conjunctival flap and autograft in term of recurrence rate and complications in primary pterygium surgery Methods: Atotal of 70 patients (thirty male and forty female) operated for primary pterygium with conjunctival autografts(in 36 eyes)or conjunctival flap (in 34 eyes) technique at AL-Hussain teaching hospital-Kerbala ,with 18 months follow up.Patients were asked for voluntary examinations of their respective ocular surface status Results: Mean age was 43.5 years(range 21-70)42.65% of the patients were male,70% of them worked predominantly out doors.Mean follow up was 12months (3-18) Recurrence rate recorded was 8.3% graft,8.8% flap,however oedema was more in graft,granuloma was nil in both Conclusions: After this long follow up period for for conjunctival flap and autograft surgeries,there was no statistically significant differences in term of the recurrence rate,as well as autograft is alonger technique with more postoperative oedema